ANALISIS FAKTOR KEUANGAN DAN NON KEUANGAN YANG MEMPENGARUHI PREDIKSI PERINGKAT OBLIGASI SYARIAH (STUDI EMPIRIS PADA PERUSAHAAN PENERBIT OBLIGASI SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012) - Ike Arisanti; Isti Fadah; Novi Puspitasari (Universitas Jember, 2014)
This study purposes to analyze the influence of financial and non financial factors to prediction of the rating Islamic bond in indonesia. The study used independent variable,that is financial factor (growth, size, profit sharing/fee, liquidity) and non financial factor ( secure and maturity) and dependent variable that is the rating of Islamic bond. This study applied logistic regresion analysis with sample collection methods using purposive sampling. After selecting fixed criterias, there were 25 Islamic bonds chosen with the numbers of 75 investigation from periods of 2010-2012. The result of this study showed that significantly effect the variable growth (X1) , size(X2), profit sharing/ fee (X3), liquidity (X4), secure (X5), maturity (X6) simultaneously to the rating prediction of Islamic bond in indonesia. Partially, variable variables of growth (X1) , size (X2), profit sharing/ fee (X3) which referred not significant affecting to the rating prediction of Islamic bond in indonesia. Meanwhile, variables of liquidity (X4), secure (X5), maturity ( X6) referred significant affecting to the rating prediction of Islamic bond in indonesia. Key word: slamic Bond rating, financial and non financialfactors, purposive sampling and logistic regression analysis.